Toward the virtual university : international online perspectives - Nistor, Nicolae, 1962-; English, Susan; Wheeler, Steve; Jalobeanu, Mihai (Emerald Publishing Limited : Information Age Pub., 2003)
This book aims to bring together the work of a number of online learning specialists from around the world, to offer the reader a global view of current and recent research and practice in electronic learning from a variety of disciplines and contexts. Some of the chapter authors indicate the likely directions e-learning may be headed in the next few years. In addition, this book is aimed at informing all those working within online learning and distance education of best practice. The content of this book will be of particular interest to university academics, researchers, college educators, K-12 teachers, education administrators and distance education students. It will also be useful as a text for those studying the management and delivery of distance education and e-learning, and indeed will be of interest to those working in all areas of education.The core of our book, the section entitled Projects and Tools, consists of research reports originally presented at the Romanian Internet Learning Workshop (RILW), an annual international conference series held in Romania between 1997 and 2001, and described in the first chapter of the volume. These projects focus on the development of instructional concepts and tools for technology-based learning environments encompassing diverse fields and disciplines from Educational Science through Intercultural Education and Foreign Languages to Beam Physics.
Keywords: Internet in higher education -- Cross-cultural studies -- Congresses.; Virtual reality in higher education -- Cross-cultural studies -- Congresses.; elektronické knihy; Conference papers and proceedings.; Web-based instruction -- Congresses.; Education -- Distance, Open & Online Education.; Open learning, distance education.; electronic books